Is vaccination against viral hepatitis B safe and immunogenic in patients with rheumatic diseases? - G. I. Gridneva; B. S. Belov; E. S. Aronova (Современная ревматология, 2024)
Impressive successes have been achieved in the fight against viral hepatitis B (HBV), but victory over this infection has not yet been achieved. According to various estimates, there are 6–12.5 times more patients with resolved HBV who are carriers of the virus than carriers of the "Australian" surface antigen HBsAg. The basis for the prevention of HBV is passive and active immunization of the population, but the data on the safety and immunogenicity of this vaccine in patients with rheumatic diseases are contradictory. This review examines the safety and immunogenicity of vaccination against hepatitis B virus (HBV) in patients with immune-inflammatory rheumatic diseases. Vaccination against HBV is indicated for patients at risk of infection and should be carried out before starting antirheumatic therapy, as immunogenicity and efficacy are significantly higher in this case. The necessity of a detailed, targeted medical history collection to clarify the risk of HBV infection before prescribing antirheumatic therapy and clarification of the immune status (presence of HBsAg, antibodies against HBc and HBs) before vaccination is emphasized.